Physiological and behavioural responses to different rearing system in broiler chickens - Norsam, Nurul Syafiqa (2017)
Floor system is commonly practiced in the Malaysian broiler industry. In a hot and humid tropical environment, broilers tend to drink more and thus water intake increases. Higher water consumption may result in wet feces and lead to litter problem. Consequently irritation to mucous membrane, stress, increase susceptibility to diseases, contact dermatitis and leg weakness in broilers. The objective of this study was to determine the welfare of broiler chickens raised on litter floor pens and battery cages under the hot and humid tropical environment. Physiological, imunological and behavioural measurements were used to assess the welfare of broilers. A total of 200 one-day-old Cobb 500 male broiler chicks were equally assigned to either battery cages with wire floors or floor pens with wood shavings as litter material. There were 10 replicates of 10 birds for each rearing system. The cages and pens were in a naturally-ventilated house and the stocking density allowed for both rearing systems was 0.1 m2/bird. Birds were fed with commercial diet and vaccinated against Newcastle disease on day 7 and 21 via intraocular route. Broilers raised on floor pens had significantly higher corticosterone (CORT), ovotransferrin (OVT) and ceruloplasmin (CPN) than their cage rearing system (CRS) counterparts on day 42. Antibody titre against ND vaccinations on day 42 was not significantly affected by rearing system. Both CRS and FRS broilers showed similar durations of tonic immobility (TI) on day 42. However, the number of inductions to elicit TI was significantly higher in CRS birds when compared to those of FRS. Mean percentages of CRS chicks resting on day 13 was significantly higher than FRS. On day 13, the FRS birds showed significantly more walking activity than the CRS group. Other behaviors were not significantly affected by rearing system on day 13. On day 27, the CRS birds spent more time feeding and drinking than their FRS counterparts. Walking and resting activities were significantly reduced in CRS birds when compared to FRS on day 27. On day 41, only resting activity was significantly affected by rearing system. The FRS birds rested more than those of CRS. Based on physiological stress and fear reactions, this study suggested that cages, while may restrict the expression of a more diverse behavioural repertoire in broilers, were better than floor pens with respect to welfare.